Enhancing Emotional Intelligence: Soft Skills Development Workshop (Emotional Intelligence Quotient) for Students - Iswardhani, Indri; Bando, Ushwa Dwi Masrurah Arifin; Nasir, Sri Astuti; Rostina; Macenning, A. Reski Almaida Dg (Abdi Cendekia : Jurnal Pengabdian Masyarakat, 2025)
The emotional intelligence (Emotional Intelligence Quotient/EQ) development workshop aimed to enhance students' soft skills. This initiative emphasized the importance of EQ in supporting academic and professional success through interactive approaches such as simulations, group discussions, and self-reflection. Needs analysis was conducted to identify improvement areas, including emotion regulation, interpersonal communication, teamwork, and conflict management. Results showed significant improvements in participants' understanding and practical skills, such as self-awareness, empathetic communication, and collaboration. Participant feedback highlighted the effectiveness of experiential learning methods. However, the workshop's one-day duration limited in-depth exploration of advanced EQ concepts. This study recommends continued training for more optimal outcomes.